2005
DOI: 10.4049/jimmunol.174.4.2412
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Basis of the Role of Diesel Exhaust Particles in Inducing Th2-Dominant Response

Abstract: There is growing evidence that diesel exhaust particles (DEP) can induce allergic diseases with increased IgE production and preferential activation of Th2 cells. To clarify the cellular basis of the role of DEP in the induction of Th2-dominant responses, we examined the effects of DEP on the cytokine production by T cells stimulated with anti-CD3/CD28 Ab and on that by monocyte-derived dendritic cells (MoDCs) stimulated with CD40L and/or IFN-γ. We examined IFN-γ, IL-4, IL-5, IL-8, and IL-10 produced by T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 35 publications
5
47
1
Order By: Relevance
“…Nasal challenge with diesel exhaust particles induces alterations in cytokine responses and an increase in IgE production (663). Diesel exhaust particles can induce allergic diseases with an increased IgE production and a preferential activation of Th2 cells (664)(665)(666). They may also act as an adjuvant of pollen allergens (667).…”
Section: Pollutantsmentioning
confidence: 99%
“…Nasal challenge with diesel exhaust particles induces alterations in cytokine responses and an increase in IgE production (663). Diesel exhaust particles can induce allergic diseases with an increased IgE production and a preferential activation of Th2 cells (664)(665)(666). They may also act as an adjuvant of pollen allergens (667).…”
Section: Pollutantsmentioning
confidence: 99%
“…One could therefore speculate that DEP exposure has an impact on several aspects of the DC biology. Indeed, in vitro data demonstrated that DEP exposure induces DC maturation (10,11) via epithelial cell-derived mediators (12,13) and that DEP-exposed DCs induce a Th2 polarization (10,(13)(14)(15).…”
Section: Once Arrived In the Mln Dcs Present The Ags To Naive T Cellmentioning
confidence: 99%
“…Studies exploring the role of DC activation and allergic risk in asthma development have focused on the adjuvant potential of PM to induce allergic sensitization to a coadministered antigen-like ovalbumin (OVA) or house dust mite [6,12,18,[28][29][30][31][32] . Often high and repeated doses of PM exposure are used that also induce tissue damage and general airway inflammation.…”
mentioning
confidence: 99%